Phenomenological Insights on Decent Work and Its Relevance to Local Economic Development - Rahman, Mizan Ikhlasul; Pahlevi, Khairi (Universitas Gadjah Mada, 2024)
The concept of decent work has few explanatory references and comparative descriptions due to limited research. So far, the concept of decent work only refers to standards and concepts issued by the International Labor Organization (ILO). Meanwhile, the Local Economic Development (LED) approach is an alternative strategy that prioritizes local aspects and resources for effective development. The research method chosen in this research is the phenomenological method. The phenomenological method explores human experiences (people’s lived experiences). This is in line with the concept of decent work and local economic development, which is highly influenced by the opinions and narratives described by the community, in this case, the research participants. This research explains the concept of decent work and local economic development based on the conditions of Banjarmasin City. It generated five explanatory clusters in this research. Cluster of general perspectives and specific perspectives related to the concept of decent work. The general perspective is that decent work should meet minimum standards and protect workers’ rights. While a specific perspective emphasizes subjectivity in viewing various decent work concepts. The other three clusters were formed from the exploration of the concept of local economic development, such as the challenge cluster, the opportunity cluster, and the relationship cluster between the concept of local economic development and decent work. These three clusters emphasize that the development concept requires comprehensive planning. Development faces challenges, such as insufficient government support, uncooperative communities, and disinterest among local people, but there are opportunities to boost local economies and improve work decency and conditions.